The Influence of Entrepreneurial Practices in Mediating Entrepreneurial Knowledge and Self-Efficacy on Student Intention in Entrepreneurship - Amalia, Riska Rossa (Jurnal Profesi Keguruan, 2025)
Entrepreneurship intention is an attraction to the world of entrepreneurship. This study aimed to analyze the influence of entrepreneurial practices in mediating entrepreneurial knowledge and self-efficacy on the entrepreneurial intention of students at SMK PGRI 01 Semarang. The research method uses a quantitative method. The population of this study was 150 male and female students in grade XI of SMK PGRI 01 Semarang. The sampling technique used the simple random sampling technique. The data collection method used a questionnaire method that had been tested for validity and reliability. The data analysis employed path analysis and hypothesis testing methods. The results of this study indicate that entrepreneurial knowledge has a positive effect on entrepreneurial intention in class XI students of SMK PGRI 01 Semarang, as self-efficacy has a positive effect on entrepreneurial intention in class XI students of SMK PGRI 01 Semarang, entrepreneurial practice has a positive effect on entrepreneurial intention in class XI students of SMK PGRI 01 Semarang, self-efficacy has a positive effect on entrepreneurial intention through entrepreneurial practice, and there is a positive influence of entrepreneurial knowledge and self-efficacy through entrepreneurial practice on entrepreneurial intention in class XI students of SMK PGRI 01 Semarang. This study suggests that schools must optimize entrepreneurial development practices by evaluating existing entrepreneurial practice learning programs, ensuring that they align with the needs and interests of students, and providing knowledge and skills relevant to their field of expertise at SMK PGRI 01 Semarang.